2018
DOI: 10.1101/503086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MYC Functions as a Switch for Natural Killer Cell-Mediated Immune Surveillance of Lymphoid Malignancies

Abstract: 34The MYC oncogene drives T and B lymphoid malignancies, including Burkitt's lymphoma (BL) 35and Acute Lymphoblastic Leukemia (ALL). Using CyTOF, we demonstrate a systemic reduction 36 in natural killer (NK) cell-mediated surveillance in SRα-tTA/Tet-O-MYC ON mice bearing MYC-37driven T-lymphomas, due to an arrest in NK cell maturation. Inactivation of lymphoma-intrinsic 38 MYC releases the brakes on NK maturation restoring NK homeostasis. Lymphoma-intrinsic 39 MYC arrests NK maturation by transcriptionally rep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Tumor‐bearing mice displayed reduced levels of interleukin (IL)‐15R⍺ + in BM stromal cells, and transgenic IL‐15 expressing mice restored NK cell anti‐tumor function indicating that IL‐15R⍺ expression BM stromal cells can be suppressed during tumorigenesis in the BM niche 23 . In support of this hypothesis, a recent study using a mouse transgenic MYC‐driven T‐lymphoma model observed reduced mNK cells in peripheral organs due to suppressed NK cell development in the BM 26 . Type I interferon (IFN) signalling was suppressed in the BM microenvironment in the presence of MYC‐driven lymphomas, and type I IFN was found to be required for systemic mNK cell development 26 .…”
Section: Nk Cell Maturation In the Tmementioning
confidence: 94%
See 1 more Smart Citation
“…Tumor‐bearing mice displayed reduced levels of interleukin (IL)‐15R⍺ + in BM stromal cells, and transgenic IL‐15 expressing mice restored NK cell anti‐tumor function indicating that IL‐15R⍺ expression BM stromal cells can be suppressed during tumorigenesis in the BM niche 23 . In support of this hypothesis, a recent study using a mouse transgenic MYC‐driven T‐lymphoma model observed reduced mNK cells in peripheral organs due to suppressed NK cell development in the BM 26 . Type I interferon (IFN) signalling was suppressed in the BM microenvironment in the presence of MYC‐driven lymphomas, and type I IFN was found to be required for systemic mNK cell development 26 .…”
Section: Nk Cell Maturation In the Tmementioning
confidence: 94%
“…23 In support of this hypothesis, a recent study using a mouse transgenic MYC-driven T-lymphoma model observed reduced mNK cells in peripheral organs due to suppressed NK cell development in the BM. 26 Type I interferon (IFN) signalling was suppressed in the BM microenvironment in the presence of MYC-driven lymphomas, and type I IFN was found to be required for systemic mNK cell development. 26 Since type I IFN is known to induce IL-15R⍺ on dendritic cells (DCs), 27 a potential decrease in IL-15R⍺ + BM DCs could explain the block in NK cell development during lymphoma development in the BM.…”
Section: Nk Cell Maturation In the Tmementioning
confidence: 99%
“…3D). Previously published experiments using this model in a MYC on vs MYC off vs murine background clearly shows a preference for lipogenesis pathway upregulation in a MYC positive state (32). Thus, in high MYC expressing lymphomas, reliance upon fatty acid synthesis could be considered a metabolic liability.…”
Section: Discussionmentioning
confidence: 82%
“…Two studies further investigated consequences of MYC overexpression on NK cell-mediated cytotoxicity. Investigating the systemic effects of Myc in murine T cell lymphomas a recent study showed that Myc expression was associated with lower NKp46 + NK cells in circulation, lower NK cell maturation and more disease progression than control mice [ 88 ]. In contrast, another study reported that MYC mRNA levels in B cell lymphomas and solid tumors are positively correlated with B7-H6 expression on the tumor cell, a ligand for the NK cell receptor NKp30.…”
Section: The Role Of Myc Overexpression On the Immune System In Lymentioning
confidence: 99%